Costs over benefits: mind wandering in sporting performance - Li, Jieling; Liu, Yafang; Xue, Shuangpeng; Tian, Bao (Frontiers in Psychology, 2024)
Athletes' mind wandering during competition has positive and negative effects. The purpose of this study was to explore the reason for these bidirectional effects. We recruited 51 athletes from China to take part in semi-structured interviews in which we explored their experiences of mind wandering in competition. We used grounded theory combined with systems thinking to complete the data analysis and theoretical construction. Results showed that the influence of mind wandering on sporting performance was dynamically influenced by "mind wandering source", "competition anxiety", "content of mind wandering", "attentional resources", and "attentional control", resulting in our development of the theory of "mind wandering in sporting performance (MWSP)". The above factors determine how mind wandering occurs and how it affects the competition. Although the occurrence of mind wandering during competition has positive effects,its negative effects cannot be ignored, which may lead to athletes losing the race (costs over benefits). Potential strategies focusing on the mitigation of negative effects and promotion of positive effects of mind wandering are discussed.